China and The Conflict in South Sudan: Security and Engagement - Ali, Moawia Ali Musa (Journal of Economic, Administrative and Legal Sciences, 2018)
This paper offers a case study of Beijing’s involvement with South Sudan, illustrating the absence of Chinese presence at the community level. The mistrust of Chinese government and China’s National Oil Companies stems from Beijing’s longstanding and historic support of Khartoum government and tacit involvement in the second civil war that generated widespread grievances amongst local communities in South Sudan. Sino-Sudanese relations amongst other factors have been the drivers of the development of South Sudanese mistrust that became barriers for Beijing, impeding it form protecting its economic investments and political interests. Chinese engagement with non-governmental actors is critical to peace. If Beijing reaches out beyond governmental actors through more integration into South Sudan’s indigenous societies, it can help bring competing groups together. Why China should be interested in getting involved in South Sudan and jeopardize its long-held non-intervention doctrine? This piece tries to answer this question under Beijing’s current international image and competition with other rivalries in the area for securing oil and strategic energy resources in the African continent.